PRINSIP IRONI BAHASA MINANG - Yessy Prima Putri (Arkhais - Jurnal Ilmu Bahasa dan Sastra Indonesia, 2022)
The Minang language is the language used by the Minangkabau community, which has around 200 million speakers. Submission of intent in a speech in the Minang language is generally done using indirect speech, figures of speech, satire/irony, and parables. The Minang community can be said to have a polite and friendly culture in the Minang language known as the phrase "muluik manih kucindan murah". The application of the principle of irony in the Minangkabau language is not the same as in Indonesian, in Indonesian, irony sentences conveyed by speakers of the meaning intended in irony figure of speech contrary to what was said/said, the interlocutor immediately understood it, while in the Minangkabau language, the interlocutor had to know the context of the conversation first, then understand what it meant. This research is a descriptive qualitative research. The data collection method used is the referential method. The method used to analyze the data in this study, namely the agih method and the matching method. The application of the principle of irony in the Minangkabau area is widely used. As far as the author observes, the application of the principle of irony is generally spoken to friends of the same age and younger than the speaker, a variety of non-formal languages ​​and tends to be rude. Hyperbole is also widely used by the Minangkabau community. In general, Minangkabau people use hyperbole to express things that contain the meaning of 'excessive'